2019
DOI: 10.1101/586693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deliver on Your Own: Disrespectful Maternity Care in rural Kenya

Abstract: 17 Background: Under the Free Maternity Policy (FMP), Kenya has witnessed an increase 18 health facility deliveries rather than home deliveries 19 with Traditional Birth Attendants (TBA) resulting in improved maternal and neonatal 20 outcomes. Despite these gains, maternal and infant mortality and morbidity rates in 21 Kenya remain unacceptably high indicating that more work needs to be done. 22 Aim: Using data from the Access to Quality Care through Extending and Strengthening 23 Health Systems (AQCESS) proje… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
(18 reference statements)
2
9
0
Order By: Relevance
“…The discrepancy might be due to good commitment of health care professionals against physical abuse. This finding is similar with studies conducted in Pakistan and India on women's experiences of mistreatment during facility based childbirth (22,23) The odds of maternal disrespect and abuse among mothers who gave birth at night shifts were 2.2 times higher than those who delivered at day shifts [AOR=2.21; 95% CI:1.306, 3.772 ].This finding in line with study conducted in Kenya (17). In line with this, qualitative study conducted in Ethiopia revealed disrespectful and abusive care were more common during night shifts(4) .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The discrepancy might be due to good commitment of health care professionals against physical abuse. This finding is similar with studies conducted in Pakistan and India on women's experiences of mistreatment during facility based childbirth (22,23) The odds of maternal disrespect and abuse among mothers who gave birth at night shifts were 2.2 times higher than those who delivered at day shifts [AOR=2.21; 95% CI:1.306, 3.772 ].This finding in line with study conducted in Kenya (17). In line with this, qualitative study conducted in Ethiopia revealed disrespectful and abusive care were more common during night shifts(4) .…”
Section: Discussionsupporting
confidence: 86%
“…This could be due to the lack of appropriate physical barriers like curtains at health facilities and/or poor understanding of the importance of confidentiality during childbirth among healthcare providers. This finding is high from the study which was conducted in urban Tanzania and Kenya (17,18).This difference might be due to data collection methods. The previous studies found data from direct observation of mothers during labor and delivery.…”
Section: Discussionmentioning
confidence: 73%
“…This substantial difference between the studies could lack of standardized definitions, instruments and study methods in a study designed disrespect and abuse during the childbirth processing at health facilities introduced the potential error in reporting estimated prevalence, affected generalizability and comparability [ 49 ]. Furthermore, this difference might be the women preferred health care providers could be preferred male in some place [ 50 ] and others could be preferred female health care providers. Besides, disrespect and abuse as normalized and internalized by both health care providers and women considered as a normal event, the way of data collection like self administration, interview and observation [ 39 ], sampling technique, sociocultural difference and way of defining of disrespect and abuse care within the studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the newborn care, there is a need for warmth, feeding support, safe oxygen use, prevention of infections etc. [26] and for the maternal, there is a need for respectful maternity care [27,28] and proper referral guidelines especially for high-risk pregnancy to a tertiary centre of prenatal care [29]. However, gaps still exists at the rural health facilities especially on the maternal care and cost-effective low-tech equipment for newborn care [26,30,31] and implementation of the referrals.…”
Section: Introductionmentioning
confidence: 99%